2013
DOI: 10.5223/pghn.2013.16.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements Use and Related Factors of Preschoolers in 3 Korean Cities

Abstract: PurposeTo estimate the prevalence of dietary supplement (DS) use, investigate the related factors associated with DS use among preschoolers and support the adequate nutrition.MethodsWe conducted a questionnaire survey of mothers of children aged between 1 and 6 years who visited pediatric clinics in 3 Korean cities (Jeonju, Suncheon, Jeongeup) between October and November 2012 at Presbyterian Medical Center. The responses from 929 questionnaires were analyzed.ResultsApproximately 45.1% of the preschoolers used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Dietary supplements (DS) or nutritional supplements contain vitamins, minerals, fiber, fatty acids, and amino-acid products, for meal replacement [ 1 ]. The use of DS has been increasing in most nations [ 2 , 3 , 4 , 5 ]. One-third of children in the United States, from infants to adolescents, have been reported to use DS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements (DS) or nutritional supplements contain vitamins, minerals, fiber, fatty acids, and amino-acid products, for meal replacement [ 1 ]. The use of DS has been increasing in most nations [ 2 , 3 , 4 , 5 ]. One-third of children in the United States, from infants to adolescents, have been reported to use DS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Korean survey from 2012 reported the prevalence of DS use in the preceding month at the level of 45% in children aged 1 to 6 years [17].…”
Section: Prevalence Of Ds Usementioning
confidence: 99%
“…Furthermore, Korean research revealed that children who attended day-care centres, children of mothers who were over 40 years old, children of mothers who used DS themselves and older children were administered DS more commonly [17]. Food allergy in the child was connected with DS administration more commonly.…”
Section: Characteristics Of the Population Which Uses Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Organs of preschool children grow fastest therefore proper nutrition is very much necessary during this period to cope up with increasing demand of the body. 3 Modern health supplements come with fortified nutrients and sugars, they are slightly expensive due to which many under privileged families in developing country like India can't afford them. Attraction of children and adolescents towards energy drinks had led to increase adverse health effects on them.…”
Section: Introductionmentioning
confidence: 99%